Preliminary investigation into subjective well-being, mental health, resilience, and spinal cord injury - Migliorini, Christine (Maney Publishing, 2013)
OBJECTIVES: To undertake a pilot investigation into whether individuals whose subjective well-being had returned to the normal homeostatic range after a spinal cord injury (SCI) may be more resilient and therefore, at less risk of emotional distress over time. To consider the relative stability of subjective well-being in individuals with chronic SCI whose subjective well-being had previously returned to the normative homeostatic range. STUDY DESIGN: Longitudinal study: Time 1 (T1) 2004 and Time 2 (T2) 2009. SETTING: Victoria, Australia. PARTICIPANTS: Participants were adults living in the community with chronic SCI, who had no mental ill-health symptoms at T1. OUTCOME MEASURES: Scales include: Comprehensive Quality of Life Scale – Adult v5 (COMQoL-A5) at T1, Personal Well-being Index (PWI – the successor to the COMQol-A5) at T2, and Depression, Anxiety & Stress Scale – short form (DASS-21) at T1 and T2. RESULTS: Twenty-one adults participated at T1 and T2. Subjective well-being was stable for 57% of the cohort. However, 19% presented with symptoms of emotional distress by T2. There was no significant difference in age (P = 0.94) or time since injury (P = 0.51) between those reporting significant emotional symptoms and those without; nor was there any systematic change in health status. CONCLUSION: This study yielded two important findings. First, individuals with chronic SCI may be vulnerable to mental health issues even after they have previously exhibited good resilience. Second, subjective well-being after SCI may not be as stable as suggested by the general quality of life literature that have examined genetic and personality connections to subjective well-being.